Kinetic resolution and parallel kinetic resolution of methyl (+/-)-5-alkyl-cyclopentene-1-carboxylates for the asymmetric synthesis of 5-alkyl-cispentacin derivatives. - Davies, S; Garner, A; Long, M; Morrison, R; Roberts, P; Savory, E; Smith, A; Sweet, M; Withey, J (2005)
Conjugate addition of lithium dibenzylamide to methyl 5-isopropyl, 5-phenyl- and 5-tert-butyl-cyclopentene-1-carboxylates occurs with high levels of substrate control (>88% de), with preferential addition to the face of the cyclic alpha,beta-unsaturated acceptor anti- to the stereodirecting 5-alkyl substituent. Treatment of a range of methyl (+/-)-5-alkyl-cyclopentene-1-carboxylates with both lithium (+/-)-N-benzyl-N-alpha-methylbenzylamide and lithium (+/-)-N-3,4-dimethoxybenzyl-N-alpha-methylbenzylamide indicates significant enantiorecognition in their mutual kinetic resolutions, with preferential addition anti- to the 5-alkyl substituent, giving the 1,2-syn-1,5-anti-arrangement (E >16) after enolate protonation anti- to the amino functionality. The kinetic resolution of a range of methyl (+/-)-5-alkyl-cyclopentene-1-carboxylates with lithium (S)-N-benzyl-N-alpha-methylbenzylamide, and their efficient parallel kinetic resolution with a pseudoenantiomeric mixture of lithium (S)-N-benzyl-N-alpha-methylbenzylamide and lithium (R)-N-3,4-dimethoxybenzyl-N-alpha-methylbenzylamide are also demonstrated, giving a range of 5-alkyl-cispentacin derivatives in >98% de and high ee after N-deprotection.